The Emergence of Bacteroides pyogenes as a Human Pathogen of Animal Origin: A Narrative Review - Carola Mauri; Chiara Giubbi; Alessandra Consonni; Elena Briozzo; Elisa Meroni; Francesco Luzzaro; Silvia Tonolo (Microorganisms)
Bacteroides pyogenes is a Gram-negative obligate anaerobe rod. It is naturally found in the oral microbiome of cats and dogs, which represents a primary source of disease for humans. The present review provides an update on the role of B. pyogenes as a pathogen responsible for infections in humans. Indeed, an increasing number of B. pyogenes infections have been reported in recent years, including skin and soft tissue infections as well as severe diseases like osteomyelitis, Lemierre’s syndrome, and bloodstream infection. Pre-analytical and analytical phases are crucial to guarantee the isolation of anaerobic bacteria, including B. pyogenes. Moreover, the introduction of MALDI-TOF mass spectrometry and 16S rRNA sequencing in clinical microbiology laboratories may be partially responsible for the increasing number of reports of B. pyogenes infections. However, the mechanisms underlying the pathogenicity of B. pyogenes remain poorly understood and require further investigations. Indeed, despite common antimicrobial susceptibilities, infections frequently persist and require multiple courses of antibiotics. In addition, based on literature data, this review indicates that treatment of skin and soft tissue infections often necessitates surgical procedures and hospitalization.